William Wordsworth - Williams, John. author. aut Link
IX, 208 p.
Keywords: In William Wordsworth, John Williams provides a detailed account of Wordsworth's evolution as a poet. This includes his earliest known writing while a pupil at Hawkshead Grammar School, and his later poetry, often virtually ignored by critics. Wordsworth's ambivalent attitude towards seeking out a public readership beyond his immediate circle of friends and admirers is a central concern of the book. This involves an assessment of the poet's shifting sense of his political allegiances alongside the pressures of personal relationships and circumstances.